Solution-processed mixed halide CH3NH3PbI3−xClx thin films prepared by repeated dip coating - Karim, A. M. M. Tanveer; Hossain, M. S.; Khan, M. K. R.; Kamruzzaman, M.; Rahman, M. Azizar; Rahman, M. Mozibur (Journal of materials science, 2019)
The mixed halide CH 3 NH 3 PbI 3−x Cl x crystalline thin film has been prepared by two-step solution-processed repeated dip coating method at an ambient atmosphere. X-ray diffraction study reveals the presence of tetragonal and cubic phases in deposited film. Raman study confirms the metal halide bond in the inorganic framework and organic CH 3 stretching/bending of C–H bond in CH 3 NH 3 PbI 3−x Cl x perovskite. Scanning electron microscopy shows that cuboid and polyhedral-like crystal grains of 100 nm to 2 μm may find applications in optoelectronics. The perovskite CH 3 NH 3 PbI 3−x Cl x thin film shows high spectral absorption coefficient of the order of 10 6 m −1 . In optical band gap study, we found the coexistence of cubic and tetragonal perovskite phases. The energy band gap is dominated by cubic phase having E g = 2.50 eV over tetragonal phase with band gap E g = 1.67 eV. The room-temperature photoluminescence study confirms band edge, shallow and deep-level emissions. The temperature-dependent cathodoluminescence study shows red, green and ultraviolet emissions. The dominating green luminescence evolved for cubic phase at 2.51 eV. The red and ultraviolet emissions are also found for mixed-phase CH 3 NH 3 PbI 3−x Cl x thin film, suitable for preparation of light-emitting devices.